1995
DOI: 10.1006/viro.1995.1166
|View full text |Cite
|
Sign up to set email alerts
|

Nef and LTR Sequence Variation from Sequentially Derived Human Immunodeficiency Virus Type 1 Isolates

Abstract: Variation in HIV-1 nef and LTR DNA sequences was assessed longitudinally during disease progression in four HIV-1-infected subjects. Point mutations were found among quasispecies obtained at a single time point in each individual, with increasing diversity with disease progression in two of three patients for whom sufficient data were available for analysis. Deletions and rearrangements were more common in late than early stages of disease. Continued sequence evolution in HIV-1 quasispecies with nef deletions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Patterns to LTR variants selected in vivo are suggested by recent studies by Ait-Khaled et al (1,2) demonstrating tissue-compartmentalized phylogenetic clustering of LTR variants in four patients and one patient, respectively. Additionally, McNearney et al (36), in evaluating LTR and Nef variability in four patients longitudinally, found increasing numbers of point and length variants with disease progression as well as greater selective constraint for the LTR sequences than for Nef. All of these studies strengthen the view that conclusions about the importance of specific sequences in the HIV-1 5Ј LTR, if based on the prototype, may not necessarily hold true for naturally occurring LTRs.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Patterns to LTR variants selected in vivo are suggested by recent studies by Ait-Khaled et al (1,2) demonstrating tissue-compartmentalized phylogenetic clustering of LTR variants in four patients and one patient, respectively. Additionally, McNearney et al (36), in evaluating LTR and Nef variability in four patients longitudinally, found increasing numbers of point and length variants with disease progression as well as greater selective constraint for the LTR sequences than for Nef. All of these studies strengthen the view that conclusions about the importance of specific sequences in the HIV-1 5Ј LTR, if based on the prototype, may not necessarily hold true for naturally occurring LTRs.…”
mentioning
confidence: 96%
“…In contrast to longitudinal studies of naturally occurring HIV-1 LTR sequences from a few patients at one stage of disease or one patient throughout a window of disease progression (1,10,11,28,(36)(37)(38), we investigated a cross section of 42 patients at all stages of HIV-1 infection. Here we report on the sequence polymorphism of 478 LTRs, on the transcription activities for a subset of these LTRs, and on altered binding of nuclear factors in vitro to some of the novel in vivo polymorphisms found to correspond with altered transcription.…”
mentioning
confidence: 99%
“…As was demonstrated in similar investigations [21,22], most if not all of the nucleotide differences seen between LTRs should be representative of LTR sequences in vivo, and not the product of nucleotide misincorporations during PCR amplification or cloning. As was demonstrated in similar investigations [21,22], most if not all of the nucleotide differences seen between LTRs should be representative of LTR sequences in vivo, and not the product of nucleotide misincorporations during PCR amplification or cloning.…”
Section: Discussionmentioning
confidence: 72%
“…As was demonstrated in similar investigations [21,22], most if not all of the nucleotide differences seen between LTRs should be representative of LTR sequences in vivo, and not the product of nucleotide misincorporations during PCR amplification or cloning. The differences between the patient LTRs and the LAI LTR were of interest because of the uneven distribution of the base pair changes.…”
Section: Discussionmentioning
confidence: 98%